Pregaming, Drinking Duration, and Movement as Unique Predictors of Alcohol Use and Cognitions Among Mandated College Students. (2nd July 2016) - Yurasek, Ali; Miller, Mary Beth; Mastroleo, Nadine; Lazar, Vanessa; Borsari, Brian
ABSTRACT: Background: Pregaming is a common phenomenon among college students and is associated with increased risks such as heavy drinking, alcohol-related consequences, and violating campus alcohol policies. However, the mechanism by which pregaming increases student risk is unclear. Objectives: The current study aimed to delineate the role of personal endorsement of pregaming, duration of an entire drinking episode on the night of an alcohol violation, and movement from one location to another in predicting alcohol use and violation-related cognitions. Methods: Participants ( N = 113) were college students who had received an alcohol violation. Hierarchical multiple regressions were conducted to investigate the predictive value of pregaming endorsement, duration of drinking, and movement on drinking behaviors [number of drinks consumed and estimated blood alcohol content (eBAC)] on the night of the alcohol violation as well as violation-related cognitions (responsibility, aversiveness). Results: Pregaming and duration of drinking were significant predictors of alcohol consumption and eBAC on the night of the violation, whereas movement was not. Duration of the drinking episode was significantly related to increased perceived responsibility for the alcohol violation. Conclusions/importance: Self-reported pregaming and the duration of the drinking episode appear to be better targets than movement for prevention and intervention efforts addressing pregaming on college campuses. Interventions should continue focusing on reducing pregaming and its associated consequences, especially for those who report a longer duration of drinking following a pregaming episode.